PTK7 Faces the Wnt in Development and Disease - Berger, Hanna; Wodarz, Andreas; Borchers, Annette (Frontiers in Cell and Developmental Biology, 2017)
PTK7 (protein tyrosine kinase 7) is an evolutionarily conserved transmembrane receptor regulating various processes in embryonic development and tissue homeostasis. On a cellular level PTK7 affects the establishment of cell polarity, the regulation of cell movement and migration as well as cell invasion. The PTK7 receptor has been shown to interact with ligands, co-receptors and intracellular transducers of Wnt signaling pathways, pointing to a function in the fine-tuning of the Wnt signaling network. Here we will review recent findings implicating PTK7 at the crossroads of Wnt signaling pathways in development and disease.